3 SUBTYPES OF ALPHA-BUNGAROTOXIN SENSITIVE NICOTINIC ACETYLCHOLINE-RECEPTORS ARE EXPRESSED IN CHICK RETINA - Keyser, K. T.; Britto, LRG; Schoepfer, R.; Whiting, P.; Cooper, J.; Conroy, W.; Brozozowskaprechtl, A.; Karten, H. J.; Lindstrom, J. (Soc Neuroscience, 1993)
A recent report described the isolation of cDNA clones encoding alpha7 and alpha8 subunits of alpha-bungarotoxin-sensitive nicotinic ACh receptors (alphaBgtAChRs) from chick brain and demonstrated that they were related to, but distinct from, the alpha subunits of nicotinic ACh receptors (nAChRs) from muscles and neurons. Monoclonal antibodies against the two alphaBgtAChR subunits were used to demonstrate that at least two subtypes are present in embryonic day 18 chicken brain. The predominant brain subtype contains alpha7 subunits, while a minor subtype contains both alpha7 and alpha8 subunits. Both subtypes may also contain other subunits. Here we report the results of immune precipitation studies and immunohistochemical studies of alphaBgtAChRs in the chick retina. In addition to the two subtypes found in brain, a new alphaBgtAChR subtype that contains alpha8 subunits, but not alpha7 subunits, was identified and was found to be the major subtype in chick retina. This subtype has a lower affinity for alpha-bungarotoxin (alphaBgt) than does the subtype containing only alpha7 subunits. Small amounts of this alpha8 subtype were also detected in brain by labeling with higher concentrations of I-125-alphaBgt than had been used previously. The subtype containing only alpha7 subunits comprised 14% of the alphaBgtAChRs in hatchling chick retina. The subtype containing alpha8 subunits (but no alpha7 subunits) accounted for 69%, and the alpha7alpha8 subtype accounted for 17%. Amacrine, bipolar, and ganglion cells displayed alpha8 subunit immunoreactivity, and a complex pattern of labeling was evident in both the inner and outer plexiform layers. In contrast, only amacrine and ganglion cells exhibited alpha7 subunit immunoreactivity, and the pattern of alpha7 subunit labeling in the inner plexiform layer differed from that of alpha8 subunit labeling. These disparities suggest that the alphaBgtAChR subunits are differentially expressed by different populations of retinal neurons. In addition, the distribution of alphaBgtAChR subunit immunoreactivity was found to differ from that of alpha-Bgt-insensitive nAChR subunits.
Keywords: ACH; BUNGAROTOXIN; NICOTINIC ACH RECEPTORS; RECEPTORS; NEUROTRANSMITTERS